A review on microalgal biomass and biodiesel production through Co-cultivation strategy. (1st September 2022) - Azarpour, Abbas; Zendehboudi, Sohrab; Mohammadzadeh, Omid; Rajabzadeh, Amin Reza; Chatzis, Ioannis
Graphical abstract: Highlights: Vital parameters affecting control and utilization of co-culture systems are evaluated. Utilization of microalgal microbial fuel cells in wastewater treatment is reviewed. Microalgal co-cultivation systems for biomass/biofuel production are analyzed. Techniques for biomass and lipid content measurement are comprehensively discussed. Current challenges and future prospects in microalgal co-cultures progress are addressed. Abstract: The adverse impacts of fossil fuels on the environment, specifically climate change, have intensified the need for finding a sustainable alternative source of energy. Numerous studies have postulated that biotechnology development, focusing on biofuel production processes, could be a suitable solution for sustainable energy production. The utilization of microorganisms, such as microalgae, is one of the basic strategies to produce biodiesel, pharmaceuticals, and nutraceuticals. Co-cultivation has overtaken mono-cultivation to improve the production of microalgae due to its endurance, foreseeability, and stability. However, further development of the co-cultivation process requires elaborate efforts to make it safe, practical, and optimal. Some dominant factors affecting the co-culture system control are the diversity of the cell groups, mass transfer, scale-up, population ratio, and time. In this review article, we will discuss some critical topics related to the co-cultivation process, such as data collection, modelling, cultivation methods, and interaction varieties. An overview of the quantification techniques for biomass concentration and lipid content is also provided. Moreover, the utilization of microalgal co-cultures will be analyzed, depicting the difficulties associated with their efficient control. As knowledge of the reactions and their entailing kinetics is elemental for analyzing the microalgal systems, which are used to synthesize intermediate products and chemicals, some studies focusing on the kinetics of microalgal biomass conversion into biofuels are presented. Since the microbial fuel cells (MFCs), as a new bioelectrochemical process, are utilized in the mixed-culture systems to treat wastewater and produce biofuels and other valuable by-products, a summary of the microalgal MFCs is also provided. Finally, arguments about the challenges and advantages of the co-cultivation systems are presented.